Analisis Hukum Islam terhadap Tradisi Makkatte Khitan Anak Perempuan Bugis - Deden Ilham Rahmani; Neni Zakiyah (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
The Makatte' Tradition of Circumcision for Bugis Girls is a traditional practice that has long been an important part of the culture of the Bugis community in Indonesia. This tradition is believed to be an obligation for all women approaching their teenage years. The aim of this research is to find out the Makatte' traditional law carried out in South Sulawesi from an Islamic legal perspective. The research method used is the normative analysis method, namely investigating facts using Al-Qur'an and hadith reasoning, applicable regulations, and maqāṣid al-syarī'ah theory. The results of this research show that in society, the makatte' tradition has five meanings: as a sign of Islam, custom or culture, a symbol of maturity, cleanliness and health, as well as religious teachings and advice. When this teaching was adopted by the community, the community believed that the series of processions had become a responsibility. Then for those who don't implement it, this will have an impact on social impacts. The Koran does not speak clearly about circumcision for either men or women. Meanwhile, the Hadith, which is the second source after the Al-Quran in Islam, speaks very little about circumcision, so it is interpreted and given the impression of only the approval of the Prophet. Islam as a natural religion certainly upholds natural values. Therefore, Islam prioritizes nobility, purity and cleanliness and perfects all aspects of life.